Measuring trade costs and gains from trade facilitation in the Philippines - Ramon L. Clarete (University of the Philippines, School of Economics (UPSE), 2017)
This paper provides estimates of trade costs of the Philippines with her key trading partners, and develops a framework for assessing their welfare cost. With tariff restrictions reduced significantly following several rounds of multilateral and regional trade negotiations, non-tariff barriers (NTBs) have emerged as key in slowing down trade flows. Given the proliferation of NTMs in the world today, chances are some of those are disguised NTBs. More importantly however, the inefficiencies associated with implementing legitimate NTMs such as the SPS on agricultural imports become unnecessary barriers to trade. This is the fat in trade costs that need to be eliminated through trade facilitation, while policy reforms would have to deal with redundant NTMs, whose claim to resources adds to the cost imposed by inefficient implementation of legitimate NTMs. This paper came up with a CGE model analytical structure for assessing the gains of lowering trade costs.
Keywords: F15; O24; 330; Trade costs; Economic development; Trade policy